UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH MELALUI STRATEGI INDEX CARD MATCH Upaya meningkatkan hasil belajar sejarah melalui strategi index card match - Zumilia Hadrann; Desma Yulia (Universitas Riau Kepulauan, 2019)
The problem of this research namely that the teacher still uses the method that has not varied, therefore the students lend tube passive, on the other hand the students will be bored in learning history because the learning process only listening, recording, and memorizing . Another problem is the absence to learn this can be seen from student learning outcomes under the KKM. The purpose of this study in accordance with the formulation of the problem then ibid research aims to determine student learning outcomes with the implementation of index card match strategy class X IPS Nahdlatul Wathan. This research uses quantitative research with a classroom action approach (PTK) using two cycles. This study uses index card match strategy. Objects in the study are various activities that occur in the classroom during the learning process. The research process is carried out in two cycles each cycle consists of four stages namely (1) planning action, (2) implementation of the action, (3) observation (observation), (4) reflection. The results of this study indicate that using the index card match strategy can improve student learning outcomes. Based on the results of research conducted over two cycles, then the end of this study concluded that the pre-action student learning outcomes were only 5 students (68,75%) and in the second cycle increased to 16 students (100%. The increase occurred after the teacher conducted and index card match strategy on history learning. Thus it can be concluded that the application of the index card match strategy can improve student learning outcomes.Keywords: Learning Outcomes, Index Card Match Strategy, MA Nahdlatul Wathan Batam.